Efficacy and Safety of Dapagliflozin versus Liraglutide in Patients with Overweight or Obesity and Type 2 Diabetes Mellitus: A Randomised Controlled Clinical Trial in Tianjin, China - Hao Zhaohu; Huang Xiao; Shao Hailin; He Feng (Journal of Diabetes Research)
Objective. We aimed to clarify the efficacy of dapagliflozin versus liraglutide in patients with overweight or obesity and type 2 diabetes mellitus (T2DM) at the beginning of the coronavirus disease 2019 (COVID-19) pandemic. Methods. T2DM patients with overweight or obesity who visited the Metabolic Disease Management Center at Tianjin Fourth Central Hospital from October 2019 to January 2020 were recruited and randomised to receive dapagliflozin or liraglutide for 24 weeks. Changes in blood glucose and lipid levels, blood pressure, and body weight, as well as the occurrence of hypoglycaemia and other adverse events, were compared. Results. 309 patients completed the study (143 in liraglutide group and 166 in dapagliflozin group). After 24 weeks, HbA1c, fasting blood glucose (FPG), and 2 h postprandial blood glucose (2hPG) levels significantly decreased from 8.80%±1.41% to 7.02%±1.05%, 10.41±3.13 to 7.59±2.16 mmol/L, and 17.90±4.39 to 10.12±2.47 mmol/L, respectively, in the dapagliflozin group, and from 8.92%±1.49% to 6.78%±1.00%, 10.04±2.99 to 7.20±1.63 mmol/L, and 17.30±4.39 to 10.13±4.15 mmol/L, respectively, in the liraglutide group. Changes in HbA1c, FPG, and 2hPG levels between groups were not significantly different. Systolic blood pressure (SBP) and low-density lipoprotein cholesterol (LDL-C) level significantly decreased from 144.1±19.1 to 139.7±16.2 mmHg (p=0.001) and from 3.21±0.94 to 2.98±0.89 mmol/L (p=0.014), respectively, in the dapagliflozin group. After COVID-19 outbreak, the number of patients taking sleep-promoting drugs increased from 4.9% to 9.4% (p=0.029). Conclusions. Liraglutide and dapagliflozin had strong hypoglycaemic effects in patients with overweight or obesity and T2DM at the beginning of the COVID-19 pandemic. Dapagliflozin may be beneficial in improving SBP and LDL-C levels; however, further research is warranted.